PERLINDUNGAN HUKUM BAGI KORBAN PEMBELIAN MOTOR CURIAN - Raden Riyan Budi Setiawan; Widhi Cahyo Nugroho (Gapenas Publisher, 2023)
Criminal justice is expected to control crime, especially against perpetrators who are victims of purchasing stolen goods, which are special crimes regulated outside the Crime codes. Basedon in the above, attracted the attention of the authors to write a thesis entitled